Short Communication: The fruit plant species diversity in the home gardens and their contribution to the livelihood of communities in rural area - Elfrida ELFRIDA; Albian Mubarak; Adi Bejo Suwardi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Elfrida, Mubarak A, Suwardi AB. 2020. Short Communication: The fruit plant species diversity in the home gardens and their contribution to the livelihood of rural communities in Tenggulun Sub-district, Aceh Tamiang, Indonesia. Biodiversitas 21: 3670-3675. Home gardens have a significant potential to improve food security and offer a contribution to household income for communities in rural areas. The aim of this study was to assess the diversity of fruit plant species in the home gardens and their contribution to the livelihood of rural communities in Tenggulun Sub-district, Indonesia. The study was conducted in three villages of Tenggulun Sub-district, Aceh Tamiang District, namely Tenggulun, Selamat, and Simpang Kiri. Extensive field surveys, plant collections, and interviews with local communities were conducted, involving 350 households, using random sampling methods. A total of 39 fruit plant species consisting of 23 genera and 17 families were recorded at the three villages. Sixteen species, i.e., A. muricata, A. jiringa, Artocarpus integer, Averrhoa bilimbi, Baccaurea motleyana, Carica papaya, Citrus aurantifolia, Citrus hystrix, Garcinia mangostana, Mangifera indica, Manilkara zapota, Musa x paradisiaca, Nephelium lappaceum, Psidium guajava, Spondias pinnata, and Syzygium aqueum were the most frequently recorded in all of the villages. In addition to being used as food, the fruit plants in the study area were also used as medicines, fodder, fuelwood, and household items. The fruit plant species have a significant role in supporting household livelihoods to improve food security and potentially offer a household income for the rural community in the study area.